A Legal Philosophy Review of the Harmonization of Bekasi City Regional Regulation and Presidential Regulation on Alcoholic Beverages - Mimin Mintarsih; Endang Sutrissno (UNIVERSITAS PAKUAN, 2026)
Alcoholic beverages have complex social and economic impacts, so their control is regulated by Presidential Regulation No. 74 of 2013 and Bekasi City Regional Regulation No. 17 of 2024. This research uses a normative juridical approach and philosophy of law to analyze the harmonization of national and local regulations. The results of the study show that the Regional Regulation is substantially in line with the Presidential Regulation, with more specific arrangements according to local needs without contradicting national policies, thus reflecting the implementation of regional autonomy in accordance with the principles of legal hierarchy. The philosophy of law approach provides a normative and reflective framework in the formation of alcohol control regulations at the national and local levels. In the context of Presidential Regulation 74/13 and the Bekasi City Regional Regulation, legal philosophy plays a role in assessing substantive justice, social benefits, and legal certainty, as well as bridging potential regulatory conflicts. With ontological, epistemological, and axiological approaches, philosophy of law helps to understand the moral and social legitimacy of alcohol control policies so that regulations are not only formal but also relevant and contextual. Keywords: Regulatory Harmonization, Hierarchy of Legislation, Philosophy of Law